Perilaku Mencuci Tangan Selama Pandemi COVID-19 - Azmiardi, Akhmad; Haryanti, Titik (HIGEIA (Journal of Public Health Research and Development), 2021)
Corona Virus Disease 2019 causes morbidity and mortality. Preventive behavior such as washing hands was known to reduce the risk of transmission of the virus. This study aimed to determine factors that influence hand washing behavior. This was an observational analytic study with cross-sectional approach conducted in Sukoharjo Regency, Central Java in April 2020. A total of 246 study subjects were obtained using online questionnaire. Factors that associated with hand washing behavior including education level >SHS (OR=2.63; 95%CI=1.04-6.63; p=0.040), income >1.8 million/month (OR=4.53; 95%CI=1.80-11.40; p=0.001), socialization of COVID-19 (OR=5.79; 95%CI=1.66-20.12; p=0.006), availability of hand washing facilities (OR=31.88; 95%CI= 2.57-395.55; p=0.007), high knowledge (OR=3.19; 95%CI=1.32-7.67; p=0.010), positive attitude (OR= 6.18; 95%CI= 2.35-16.20; p<0.001), high threat perception (OR=4.36; 95%CI=1.72-11.00; p=0.002). In conclusion, education >high school, income level >1.8 million/month, socialization about COVID-19, availability of hand washing facilities, high knowledge, positive attitude and high threat perception increase hand washing behavior during the COVID-19 pandemic. Keywords: Factors, Hand Washing, COVID-19